Anodization of sputtered metallic films: The microstructural connection. (August 2015) - Choudhury, Tanushree H.; Raghavan, Srinivasan
Abstract : A simple microstructural rationale for successful anodization of metallic films into ordered oxide nanostructures has been identified. It applies to three of the most commonly studied systems, Zr, Ti and Al films and can be extended to other such oxides. A dense Zone T or II microstructure, in sputtered films, is the most critical ingredient. While T substrate  > 0.3 T melting is the simplest route, pressure and plasma heating can also be exploited. Such microstructures are also associated with a unique growth stress signature.